Inequities in breast cancer outcomes in Chile: An analysis of case fatality ratios and survival rates (2007–2018) - Benjamín Madariaga; Susana Mondschein; Soledad Torres (PLoS ONE, 2025)
Breast cancer is a leading cause of illness and death among women in Chile, yet national data on health outcomes remain limited in the absence of a cancer registry. This observational study examines disparities in breast cancer case fatality ratios and survival rates by health insurance provider and geographic region using national hospital discharge and mortality databases from 2007 to 2018. We analyzed 58,254 hospital discharges and 16,615 deaths related to breast cancer. Case fatality and survival estimates were computed using crude ratios, Kaplan-Meier methods, and Cox proportional hazards models. Nationally, the average case fatality ratio was 26.8 percent. Patients in the public health insurance system had significantly higher fatality ratio (27.5 percent) than those in the private system (15.7 percent). One- and five-year survival rates were lower for publicly insured patients (93.4 percent and 80.8 percent) than for privately insured patients (97.3 percent and 90.2 percent). Within the public system, survival varied by income-based segment, with the lowest rates among the most socioeconomically disadvantaged group. Patients in the Metropolitan Region showed better survival compared to those living in other regions. Cox regression analysis confirmed that health insurance type, age, year of diagnosis, and region of residence were significant predictors of survival. These findings suggest that, despite universal health guarantees in Chile, meaningful inequities in breast cancer outcomes persist. The methodology used in this study relies on administrative data and can be applied in other countries or regions with access to comparable hospital discharge and mortality records, supporting broader efforts to monitor and reduce healthcare disparities.